The role of functional health literacy in long-term treatment outcomes in psychosocial care for adolescents. - Beukema, L.; Reijneveld, S. A.; Jager, M.; Metselaar, J.; de Winter, A. F. (European Child & Adolescent Psychiatry, 2020)
Although among adolescents with psychosocial problems low health literacy may increase the risk of poor treatment outcomes, the contributing mechanisms within treatment remain unclear. A better understanding of these mechanisms could contribute to improved treatment processes and outcomes. This study aims to examine the relationship between functional health literacy, treatment processes (treatment adherence, learning processes), and treatment outcome (level of psychosocial problems) in adolescents in psychosocial care. We used data from a prospective cohort study among adolescents aged 12–18 (N = 390), collected in four successive measurements: at entry into care, and 3, 12, and 24 months thereafter. We used a mixed effect model to investigate the association between level of functional health literacy (adequate vs. inadequate) and treatment processes (treatment adherence, learning processes) and treatment outcome (level of psychosocial problems). Between adolescents with adequate and inadequate functional health literacy, we found no differences or change over time in adherence or learning processes. The level of psychosocial problems significantly declined over time (β = − 1.70, 95% CI [− 2.72, − 0.69], p =.001) to a similar degree in both groups, though, in all measurements, the level was consistently higher for adolescents with inadequate health literacy. We conclude that health literacy levels did not affect change in treatment processes nor in outcomes of psychosocial treatment. However, the consistently higher level of psychosocial problems among adolescents with inadequate health literacy suggests an unaddressed need in psychosocial care.